2020
DOI: 10.1111/jnc.15023
|View full text |Cite
|
Sign up to set email alerts
|

What works and what does not work in Alzheimer’s disease? From interventions on risk factors to anti‐amyloid trials

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder with no approved disease-modifying therapy (DMT). In this review, we summarize the various past approaches taken in an attempt to find treatments capable of altering the longterm course for individuals with AD, including: translating epidemiological observations into potential treatment options; seeking a single-treatment approach across the continuum of AD severity; utilizing biomarkers for assessing target engagement; using biomarkers as ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 126 publications
(294 reference statements)
0
24
0
1
Order By: Relevance
“…1163 Developing disease-modifying therapies for AD presents an immense challenge, with little success despite intense work over decades. 314,[1164][1165][1166][1167] Some of the reasons why drug development for AD continues to fail include: (a) in vitro experiments poorly mimic in vivo conditions, (b) Aβ and tau exist in multiple covalent and aggregated forms of uncertain relevance to pathology and we have a poor knowledge of their structures, and (c) the limitations of animal models. 314 Amongst animal models, genetically-modified mouse lines are invaluable and widely used models for understanding genes, proteins, and biological pathways, evaluating disease progression, and assessing safety of molecules for therapeutic purposes in many diseases including neurodegenerative diseases, cancer and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…1163 Developing disease-modifying therapies for AD presents an immense challenge, with little success despite intense work over decades. 314,[1164][1165][1166][1167] Some of the reasons why drug development for AD continues to fail include: (a) in vitro experiments poorly mimic in vivo conditions, (b) Aβ and tau exist in multiple covalent and aggregated forms of uncertain relevance to pathology and we have a poor knowledge of their structures, and (c) the limitations of animal models. 314 Amongst animal models, genetically-modified mouse lines are invaluable and widely used models for understanding genes, proteins, and biological pathways, evaluating disease progression, and assessing safety of molecules for therapeutic purposes in many diseases including neurodegenerative diseases, cancer and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six of the monoclonals clearly recognize an Aß-related epitope that is located in the amino terminal ( 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ) or central ( 7 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ) third of the molecule or both ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Monoclonal antibodies against Aß are a leading class of therapeutic for AD. Many of these antibodies have been evaluated in clinical trials, but so far none have demonstrated consistent therapeutic activity in slowing the progression of AD and none have been approved by the FDA (reviewed in (4,5)). Conformation-dependent monoclonal antibodies against Aβ are also an invaluable tool for research in the role of amyloids in Alzheimer's disease because they recognize epitopes that are differentially displayed on distinct structural polymorphs or folded states of the peptide, providing insight into the role of polymorphisms in the pathogenic spectrum of the disease (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoclonal antibodies against Aß are a leading class of therapeutic for AD. Many of these antibodies have been evaluated in clinical trials, but so far none have demonstrated consistent therapeutic activity in slowing the progression of AD and none have been approved by the FDA (reviewed in (4,5)).…”
Section: Introductionmentioning
confidence: 99%